Analisis Kepentingan Sudan dalam Pembukaan Hubungan Diplomatik dengan Israel Tahun 2020 - Soeryana, Larissa Amelinda; Windiani, Reni; Paramasatya, Satwika (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
Since it reached it’s Independence, for years, Sudan hasn’t only been active on sendingaids to Palestine and actively advocating Palestine’s independence on InternationalOrganizations, but also, Sudan made a regulation on boycotting Israel. At the year of2020, in all of a sudden, Sudan opened a diplomatic relation with Israel. This causedpeople to question because Sudan has been supporting Palestine for years and Israel isPalestine’s mortal enemy. This research is aiming to find the reasons behind Sudan’sdecision on opening a diplomatic relation with Israel. With the datas that are collectedfrom books and news, it’s found that not only that Sudan has been struggling domesticallysince it’s independence, but also since the separation of the North and South Sudan, it’sdomestic situation has only been going worse. In this position, Sudan’s only hope was toget help from other country, but this option is impossible to achieve because Sudan is stillin the US’s terrorist list. Based on the facts found, it can be concluded that the openingof the diplomatic relation between Sudan and Israel was based on Sudan’s rational wayof making decisions to achieve it’s national interest, which was to save and strive for it’scountry’s existance.